'Freedom of the seas': Woodrow Wilson and natural resources. (2nd October 2018) - Dodsworth, Ashley
Abstract : 'Probably no American of the twentieth century has received more scholarly attention than Woodrow Wilson' [L.E. Gelfand, 'When Ideals Confront Self-Interest: Wilsonian Foreign Policy', Diplomatic History 18, no. 1 (1994): 125–34, 125] yet this scholarly attention has yet to consider the role that natural resources played in Wilson's understanding of the world, or to examine how his understanding of concepts that were central to his political writing and decisions, such as self-determination, were tied to access to natural resources. This article will fill this gap and sketch out how both Wilson and 'Wilsonianism' consider natural resources and the implications of this.